Transformasi Limbah Organik Rumah Tangga Ramah Lingkungan Dengan Metode Eco Enzyme - Theresye Yoanyta Octora; Amrulloh Ibnu Kholdun; Muhammad Dheo Saputra; Akbar Taufiqul Hakim; Lukmanul Hakim Drihim (Jurnal Abdimas Transportasi & Logistik, 2022)
During the Covid-19 pandemic, Tourism in Pangandaran was at a loss and even threatened to go bankrupt, the surrounding community who previously supported families from the tourism sector were forced to weaken their economy because they followed the rules for the Implementation of Community Activity Restrictions (PPKM). Eco Enzym is a product of waste management and processing that can be used as liquid fertilizer, bar soap, dish soap, repellent, disinfectant. The purpose of this Community Service (PkM) activity is to provide innovation and solutions to answer problems that occur in the community around Nusawiru Airport, Pangandaran and the community can be creative and innovative to make eco enzym products into products worth selling. This PkM uses the method of socialization and providing information in the form of education with leaflet media, the practice of making and distributing processed products from eco enzym. PkM will be held in the meeting room at Nusawiru Airport, Pangandaran on Thursday, July 7, 2022, from 09.00 to 15.00 WIB. The parameters for the success of this PkM activity are that the participants meet the target of 20 people, the community is enthusiastic about being able to manage and process waste into eco enzym and the community's understanding of the product results obtained from eco enzym and the benefits of eco enzym.